ABOUT SOLUTIONS OF THE NONLINEAR DIFFERENTIAL SYSTEMS - MACUROVÁ, Anna; MACURA, Dušan (Trends in education, 2008)
In the article are defined some properties of the solutions systems differential equations.
Keywords: Differential equations; properties of the solutions.